PERANAN MANAJEMEN INOVASI DALAM MENINGKATKAN KINERJA ORGANISASI PENDIDIKAN DI SALAH SATU SEKOLAH SMP SWASTA KOTA TEBING TINGGI - Harahap, Khairunnisa; Sukma, Dasmara; Lubis, Septi Aulia (Yayasan Pendidikan Islam Akmalia, 2022)
Innovation is an idea, idea, practice or object/object that is realized and accepted as something new by a person or group for adoption. Innovation is an idea, practice, or object that is perceived as new by an individual or other unit of adoption. Innovation is an idea, item, event, method, which is felt or observed as something new for a person or group of people (society), whether it is the result of an invention or discovery. Innovation is held to achieve certain goals or to solve a certain problem. Educational innovation is innovation in the field of education or innovation to solve educational problems. Educational innovation is an idea, item, method that is felt or observed as new for a person or group of people (society), either in the form of invention (new discoveries) or discovery (newly discovered people), which are used to achieve goals or to solve problems faced.